Faktor Yang Mempengaruhi Keputusan Melakukan Transfer Pricing - Novilia, Hellen; Sufiyati, Sufiyati (GEMA EKONOMI, 2023)
Transfer pricing is one of the factors that affect company profitability, even to state tax revenues. The purpose of this study is to find out how profitability, company size, tunneling incentive, and tax avoidance affect company decisions in carrying out transfer pricing practices. This study uses multiple linear regression methods by utilizing secondary data obtained from financial reports or annual reports. The subjects of this research are non-cyclical consumer companies listed on the Indonesia Stock Exchange (IDX) based on their 2019-2021 financial reports. The results of this study are that tax avoidance has an effect on transfer pricing practices, while profitability, firm size, and tunneling incentive have no effect on transfer pricing practices